b - Zoehfeld, Kathleen Weidner (New York : Scholastic, 2006)
Text and photographs describe the behaviors and physical characteristics of penguins.
Text in Arabic.
K-3
Translation of: Penguins.
Title supplied by OCLC WorldCat.
Keywords: Penguins; Arabic language materials; Penguins; Arabic language